Derivation and internal validation of a clinical prediction rule to identify patients with low risk of recurrent venous thromboembolism who can discontinue oral anticoagulants after five to seven months of treatment for unprovoked venous thromboembolism - Betancourt, Marisol (University of Ottawa (Canada), 2007)
Background. Whether to continue or to discontinue oral anticoagulation therapy (OAT) after 6 months of treatment to prevent recurrent or fatal events in unprovoked VTE patients is currently controversial. We sought to develop and internally validate a clinical prediction rule (CPR) to identify patients at low risk of recurrent VTE (at most 3% annual risk) for whom OAT could be safely discontinued. Methods. Univariate and multivariate analysis techniques were used to identify the best set of predictor variables. Results and conclusions. We derived and internally validated a CPR for females comprised of D-Dimer over 250 ug/L, post-thrombotic signs present, older age (over 65 years) and obesity (BMI over 30 kg/m2). Women with one or none of the four aforementioned clinical predictors had an annual risk of recurrent VTE of 1.6% and may be able to discontinue OAT. None of the models for males was shown to be safe.
Keywords: Health Sciences, Epidemiology.